Biochemical and Mutagenic Effects of 'Khat' (Catha Edulis) in Rats. - Al-Zubairi, Adel Sharaf (2007)
Khat leaves were originally used as a stimulant and a remedy against diseases and khat chewing became a widespread habit that has a deeprooted sociocultural tradition in Africa and the Middle East. The present study was undertaken to evaluate the biochemical and toxicological effects of crude Catha edulis extract sub-acute (7 weeks) administration and to investigate the biochemical, toxicological and mutagenic effects of Catha edulis crude extract sub-chronic (13 weeks) administration in rats. Seventy four Sprague-Dawley male rats were used in this study. The sub-acute treatment group (38 rats) was further divided into 4 groups (control group and 500, 1000 and 2000 mglkg body weight treatment groups), while the subchronic treatment study group (36 rats) was subdivided into three further groups (control group and 1000 and 2000 rnglkg body weight treatment groups). For genotoxicity assessment we used chromosomal aberrations assay (CAs) and single cell gel electrophoresis assay (SCGE), the comet assay. Body weight changes and food consumption were found to be not significantly different among all treatment groups when compared to the corresponding controls. We estimated the lipid peroxidation products, as a biomarker of oxidative stress and free radical activity, malondialdehyde, MDA (measured as plasma TBARS) and the results in the sub-acute (7 weeks) treatment group were found to be non-significantly different compared to the control group, while in the 13 weeks treatment groups, MDA levels in the 1000 and 2000 mglkg body weight treatment groups were found to be significantly (P < 0.05) lower, by 28% and 30% respectively, compared to the control group. Lipid profiles, uric acid, albumin, liver enzymes activities and total and prostatic acid phosphatase (ACP) results in the sub-acute treatment groups were found to be non-significantly affected compared to the control group. In contrast testosterone was found to be 2.8 and 2.4 folds significantly higher (P< 0.01) in the 1000 and 2000 mglkg body weight treatment groups respectively, compared to the control group. These levels were also found to be increased in the 500 mglkg body weight treatment by 54% compared to the control group although the increase was not significant. Results of serum total cholesterol and HDL cholesterol concentrations after 13 weeks treatment with Catha edulis crude extract were found to be significantly higher by 18% and 15% respectively (P< 0.05), in the 1000 mg/kg body weight treatment group compared to the control group. For the genotoxicity assessment tests we observed conflicting results between the CAs and comet assay. The results of CAs assay in the 2000 mg/kg body weight treatment group were found to be significantly higher (7.38%) compared to the control group (2.2%) (P< 0.05), while in the 1000 mg/kg body weight treatment group 2.5% aberrated metaphases were observed. On the other hand results of DNA damage in the comet assay were observed to show no significant difference between treatment and control groups. However the predominant chromosomal aberrations scored in the CAs were chromatoid gaps followed by chromatoid breaks. We can conclude that Catha edulis leaves contribute antioxidant properties due to its polyphenolic constituents as well as testosterone up-regulation. Further investigations are recommended to elucidate the effects of fresh leaves of Catha edulis on chromosomes and other biomolecules using molecular techniques.